Rapid plastic breeding response to rain matches peak prey abundance in a tropical savanna bird. Issue 11 (12th August 2019) - Hidalgo Aranzamendi, Nataly; Hall, Michelle L.; Kingma, Sjouke A.; van de Pol, Martijn; Peters, Anne
Abstract: Changes in climate are shifting the timing of life cycle events in the natural world. Compared to northern temperate areas, these effects are relatively poorly understood in tropical and southern regions, where there is limited information on how timing of breeding and food availability are affected by climatic factors, and where patterns of breeding activity are more unpredictable within and between years. Combining a new statistical modelling approach with 5 years of continuous individual‐based monitoring of a monsoonal tropical insectivorous bird, we quantified (a) the proximate climatic drivers at two trophic levels: timing of breeding and abundance of arthropod prey; (b) the effect of climate variation on reproductive output and (c) the role of individual plasticity. Rainfall was identified as the main determinant of phenology at both trophic levels. Throughout the year, likelihood of egg laying increased very rapidly in response to even small amounts of rain during the preceding 0–3 weeks. Adult body mass and male sperm storage also increased rapidly after rain, suggesting high breeding preparedness. Additionally, females were flexible, since they were more likely to nest whether their previous attempt was longer ago and unsuccessful. Arthropod abundance also increased after rainfall, but more slowly, with a peak around 10 weeks. Therefore, the peak food availability coincided with the presence of dependent fledglings. Fitness benefits of nesting after more rain appeared to be linked to offspring quantity rather than quality: nest attempts following higher rainfall produced larger clutches, but showed no improvement in nestling mass or relative fledging success. The response of clutch size to rainfall was plastic, since repeated sampling showed that individual females laid larger clutches after more rain, possibly mediated by improved body mass. Rapid, individually flexible breeding in response to rainfall and slower increase in arthropod abundance also as a response to rainfall, might buffer insectivorous species living in tropical seasonal environments from climate change‐induced phenological trophic mismatches. Abstract : This article presents the first quantitative evidence that rainfall drives timing of breeding and food abundance in a tropical bird with no effect of temperature on breeding. The authors show that insectivorous birds of tropical savanna can quickly start laying eggs, that is by increasing body mass (males and females) and cloacal protuberances in response to rain.